PENGARUH MODEL RUDIE TERHADAP KEMNDIRIAN DIGITAL SISWA - Ihwono, Rudi; Mochamad Cholily, Yus; Syaifuddin , Mohammad (JS (JURNAL SEKOLAH), 2025)
Abstract: This study aims to examine the effect of the RUDIE Model on the digital independence of eleventh-grade students in Informatics subjects, specifically in algorithms and programming material, at SMA Muhammadiyah 1 Gresik. The study is motivated by the low digital independence of students, particularly in utilizing digital resources. One of the causes is the students' lack of familiarity and the low utilization of technology effectively in learning. Based on the results of research using a quantitative method with a quasi-experimental design, involving pre-test and post-test on two groups, a significant increase in digital independence scores was found in the experimental class. The t-test results show a significance value of < 0.05, indicating a significant difference between the two classes. The application of the RUDIE Model has proven to be effective in improving students  digital independence, which, in turn, prepares them to face challenges in the increasingly complex information era. This model focuses on developing students skills in utilizing digital technology independently, which is crucial for the advancement of education in the future.  Keyword: RUDIE Model; Digital Independence; Digital Resources   Abstrak:  Penelitian ini bertujuan untuk pengaruh Model RUDIE terhadap kemandirian digital siswa kelas XI pada mata pelajaran Informatika materi algoritma dan pemrograman di SMA Muhammadiyah 1 Gresik, dilatarbelakangi rendahnya kemandirian digital siswa terutama dalam aspek pemanfaatan sumber digital. Salah satu penyebabnya adalah  belum terbiasanya siswa dan rendahnya pemanfaatan teknologi secara efektif dalam pembelajaran. Berdasarkan hasil penelitian yang menggunakan metode kuantitatif dengan desain eksperimen semu (quasi-experiment), yang melibatkan pre-test dan post-test pada dua kelompok, ditemukan adanya peningkatan skor kemandirian digital yang signifikan pada kelas eksperimen. Hasil uji-t menunjukkan nilai signifikansi < 0,05, yang berarti terdapat perbedaan yang signifikan antara kedua kelas. Penerapan Model RUDIE terbukti efektif dalam meningkatkan kemandirian digital siswa, yang pada gilirannya mempersiapkan mereka untuk menghadapi tantangan di era informasi yang semakin kompleks. Model ini berfokus pada pengembangan keterampilan siswa dalam memanfaatkan teknologi digital secara mandiri, yang sangat penting untuk perkembangan pendidikan di masa depan Kata Kunci: Model RUDIE; Kemandirian Digital; Sumber Digital